2021
DOI: 10.37868/hsd.v3i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency of Maritime English course: An investigation in Istanbul, Turkey

Abstract: Effective communication in the sea and ocean can only be achieved through a common language. Maritime professions in Turkey for many years have been seen as an important area of employment. Maritime vocational and technical high schools are also seen as educational institutions that play an important role in this field. In this study, it has been aimed to define the level of general and Maritime English education provided by the maritime vocational high schools, the problems and deficiencies of education, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…This image evokes many associations in the British's minds; it can be associated with various objects and become an impetus for creating various poetical images. Maritime images in English poetry are closely connected with the folk tradition (Saray et al, 2021). It is a well-known fact that ancestors especially revered freshwater as a source of life and a boundary between the world of the living and the dead.…”
Section: Figure 1 Semantic Classification Of Nature Symbolsmentioning
confidence: 99%
“…This image evokes many associations in the British's minds; it can be associated with various objects and become an impetus for creating various poetical images. Maritime images in English poetry are closely connected with the folk tradition (Saray et al, 2021). It is a well-known fact that ancestors especially revered freshwater as a source of life and a boundary between the world of the living and the dead.…”
Section: Figure 1 Semantic Classification Of Nature Symbolsmentioning
confidence: 99%
“…According to the characteristics and requirements of online teaching and ME, Aydin et al [20] suggested that online oral communication plays a vital role in ship-based external communication and the minimum requirements for ME training. Saray et al [21] assessed the level of general English and ME education at the Maritime Vocational College in Istanbul, Turkey, the shortcomings of education, and measures to improve the quality of education. Ahmmed et al [22] applied a hybrid approach to understanding the ME skills needed by Bangladeshi seafarers for them to work onboard and increase employability in the maritime sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Self-organizing refers to a system's ability to create its own organization, independent of top-down control, by following a set of simple rules that enables collaboration" (Conway et al, 2011). The following ones are among them, namely: space, knowledge and cooperation (Saray et al, 2021). Knowledge management in the context of a large amount of information is a particularly important prerequisite for the effectiveness of autonomy.…”
Section: "Online Lab" Modelmentioning
confidence: 99%